2018
DOI: 10.3390/ijms19113438
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soybean Genes Whose Expression is Affected by the Ensifer fredii HH103 Effector Protein NopP

Abstract: In some legume–rhizobium symbioses, host specificity is influenced by rhizobial nodulation outer proteins (Nops). However, the genes encoding host proteins that interact with Nops remain unknown. We generated an Ensifer fredii HH103 NopP mutant (HH103ΩNopP), and analyzed the nodule number (NN) and nodule dry weight (NDW) of 10 soybean germplasms inoculated with the wild-type E. fredii HH103 or the mutant strain. An analysis of recombinant inbred lines (RILs) revealed the quantitative trait loci (QTLs) associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 86 publications
(107 reference statements)
1
18
0
Order By: Relevance
“…The QTL and candidate genes underlying the symbiosis-related traits were identified in recombinant inbred lines (RILs) based on a linkage map with SNP markers. The responses of QTL to NopL, NopP, and NopD have been studied (Wang et al 2018;Zhang et al 2018;Wang et al 2020). Although previous research has identified several QTL associated with symbiosis-related traits in soybean, more work is needed to identify the genes involved in QTL responses to different T3Es.…”
Section: Introductionmentioning
confidence: 99%
“…The QTL and candidate genes underlying the symbiosis-related traits were identified in recombinant inbred lines (RILs) based on a linkage map with SNP markers. The responses of QTL to NopL, NopP, and NopD have been studied (Wang et al 2018;Zhang et al 2018;Wang et al 2020). Although previous research has identified several QTL associated with symbiosis-related traits in soybean, more work is needed to identify the genes involved in QTL responses to different T3Es.…”
Section: Introductionmentioning
confidence: 99%
“…To detect the QTL underlying nodule-related traits, a composite interval mapping method was used with WinQTL Cartographer (Wang et al, 2018;Zhang et al, 2018). The detailed parameters followed the published method (Zhang et al, 2018).…”
Section: The Conditional Quantitative Trait Locus Mapping Of Nodulatimentioning
confidence: 99%
“…The differences in phenotypic values were used to determine the location of conditional QTL. At the same time, the phenotype differences in RILs inoculated with HH103 TtsI or the parental strains were used to determine the conditional QTL's location (Wang et al, 2018). The detailed method is as follows.…”
Section: The Conditional Quantitative Trait Locus Mapping Of Nodulatimentioning
confidence: 99%
See 2 more Smart Citations